2015
DOI: 10.1038/ctg.2014.18
|View full text |Cite
|
Sign up to set email alerts
|

Medication Risk-Taking Behavior in Functional Dyspepsia Patients

Abstract: Objectives:No medication is approved for the treatment of functional dyspepsia (FD). The risks that patients would be willing to take to cure their FD symptoms are unknown.Methods:FD patients (Rome III criteria) were mailed a questionnaire that assessed demographics, medication use, and prior medication adverse events. Scales to measure FD severity, quality of life, anxiety, depression, impulsiveness, and risk-taking behavior were included. A standard gamble (SG) evaluated willingness to take risks associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 24 publications
0
17
0
Order By: Relevance
“…Given the limited efficacy of the majority of conventional medical therapies, it is not surprising that up to 50% of patients with functional dyspepsia seek out other forms of treatment 71 ; in one study, nearly 50% of the patients were willing to accept a 12.7% risk of sudden death with a drug that offered a 99% chance of cure, 72 in the hope of improving their symptoms and quality of life. However, consistent evidence of the efficacy of acupuncture, homeopathy, or probiotics in functional dyspepsia is lacking.…”
Section: Complementary and Alternative Therapymentioning
confidence: 99%
“…Given the limited efficacy of the majority of conventional medical therapies, it is not surprising that up to 50% of patients with functional dyspepsia seek out other forms of treatment 71 ; in one study, nearly 50% of the patients were willing to accept a 12.7% risk of sudden death with a drug that offered a 99% chance of cure, 72 in the hope of improving their symptoms and quality of life. However, consistent evidence of the efficacy of acupuncture, homeopathy, or probiotics in functional dyspepsia is lacking.…”
Section: Complementary and Alternative Therapymentioning
confidence: 99%
“…These novel results extend recent findings that patients with chronic gastrointestinal disorders such as irritable bowel syndrome and functional dyspepsia consider their symptoms severe enough that they would be willing to exchange a longer lifespan for better health and quality of life. For example, patients with irritable bowel syndrome reported that they would accept a median 1% risk of sudden death for a 99% chance of cure of their irritable bowel syndrome symptoms, while patients with functional dyspepsia were willing to accept a 12.7% risk of sudden death for a chance to cure their symptoms . Crohn's disease patients have indicated that they are willing to accept increased serious adverse event risks in exchange for clinical efficacy …”
Section: Discussionmentioning
confidence: 99%
“…For example, patients with irritable bowel syndrome reported that they would accept a median 1% risk of sudden death for a 99% chance of cure of their irritable bowel syndrome symptoms, 18 while patients with functional dyspepsia were willing to accept a 12.7% risk of sudden death for a chance to cure their symptoms. 19 Crohn's disease patients have indicated that they are willing to accept increased serious adverse event risks in exchange for clinical efficacy. 17 Our hypothesis was confirmed with a significant association between symptom severity and medication risk acceptance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations